Assessment of Risk Factors of Hepatitis B; A Case-Control Study - Adnan, Fakhar Uz Zaman, Imran Khuwaja, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Global health is facing numerous health problems but Hepatitis B Virus is regarded as a major health concern because it has manifested among 7% of the world's population. The majority of people who are infected with this virus are reported from developing countries and they have little to no access to medical facilities; their options of getting a proper treatment are minimal. Hepatitis B Virus is a blood-borne disease; it is transmitted from person-to-person through contact and practices that involve the exchange of body fluids such as unsafe sex or blood transfusions of an infected person. Vertical transmission can also aid in the spreading of the Hepatitis B Virus, contaminated needles used in the injection of drugs or infected needles used for tattoos can also be fundamental tools for spreading this virus. This study was done to assess and find the risk factors for hepatitis B in the region of Abbottabad district. Methods: A case-control study was done among the patients visiting Ayub Teaching Hospital for regular checkups. The sample included 80 cases and 80 controls. The non-probability convenient method was used as a sampling technique. Data was collected using a structured questionnaire. Data were analyzed using SPSS Statistics 23 and frequencies, mean, standard deviation, p values, and odds ratios were calculated. Results: A total of 80 cases and 80 controls were taken (Male to female ratio was 1:4). The mean age of patients was 38.74 ± 13.597. The frequency of age ranging from age 18 to 30 was maximum. Odds ratios and p values were calculated for different risk factors. The odds ratio for the history of blood transfusion was 1.581. Patients who had family members with hepatitis B had a p-value of 0.002. Those who share toothbrushes had an odds ratio of 1.116. Individuals who used illicit injectable drugs had an odds ratio of 2.206. Patients with a history of dental procedures had an odds ratio of 1.581. People with tattoos, ear, and nose piercings had an odds ratio of 1.527. Patients with a history of surgical procedures had an odds ratio of 1.165. Conclusion: This study showed that those patients who received a blood transfusion are at more risk of getting hepatitis B infection. Similarly, patients who live with hepatitis B patients or those who have infected family members are at risk. Sharing toothbrushes, and using illicit injectable drugs are at risk. Patients with a history of dental or surgical procedures are also at risk of developing hepatitis B. Keywords: HBV (hepatitis B virus), HBsAg (hepatitis B surface antigen), Risk factors